2014
DOI: 10.1016/j.jprot.2013.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the mevalonate pathway enzymes in the Lutzomyia longipalpis (Diptera: Psychodidae) sex pheromone gland demonstrated by an integrated proteomic approach

Abstract: In Latin America, Lutzomyia longipalpis is the main vector of the protozoan parasite Leishmania infantum, which is the causal agent of American Visceral Leishmaniasis. This insect uses male-produced pheromones for mate recognition. Elucidation of pheromone biogenesis or its regulation may enable molecular strategies for mating disruption and, consequently, the vector's population management. Motivated by our recent results of the transcriptomic characterization of the L. longipalpis pheromone gland, we perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 84 publications
(88 reference statements)
0
11
0
Order By: Relevance
“…Three gels from three independent midgut suspensions were performed. Proteins were enzymatically digested following procedures previously described [ 35 ] with some modifications. Briefly, fine slices from each protein lane were manually excised and de-stained three times in 400 μL of 50 % acetonitrile, 25 mM NH 4 HCO 3 pH 8.0 for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Three gels from three independent midgut suspensions were performed. Proteins were enzymatically digested following procedures previously described [ 35 ] with some modifications. Briefly, fine slices from each protein lane were manually excised and de-stained three times in 400 μL of 50 % acetonitrile, 25 mM NH 4 HCO 3 pH 8.0 for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…The costs of production are rarely demonstrated in insects (but see Johansson et al [94]), however these can be inferred indirectly in species where signal production commences after adult eclosion (as is the case for L. longipalpis [83]). Recent transcriptomics and proteomics studies have revealed much about the biosynthetic pathway for glandular secretions in Lutzomyia including the specific enzyme pathways involved in sesquiterpenoid biosynthesis [95, 96]. It was observed in L. longipalpis that if the diet is changed, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In L. longipalpis it is conceivable that an analogous process is occurring. González-Caballero [95] and colleagues used transcriptome and proteome data to explore the enzymatic cascade from the sex pheromone gland. Molecules which are associated with enzymes of the mevalonate pathway were found in the pheromone gland.…”
Section: Introductionmentioning
confidence: 99%
“…The proteins were re-suspended in buffer containing 0.5 M Hepes and 7 M urea, and the protein concentration was determined using Qubit. The proteins were enzymatically digested in a solution following previously established protocols [ 37 ] with some modifications. Briefly, the proteins were reduced in 65 mM DTT for 30 min at 56 °C and then alkylated with 200 mM iodoacetamide at 25 °C in the dark for 30 min.…”
Section: Methodsmentioning
confidence: 99%